Association between blood selenium levels and gestational diabetes mellitus: A systematic review and meta-analysis - Yan, Shuai; Su, Han; Xia, Yang; Yan, Zixuan; Gao, Yitao; Shi, Mengyuan; Liu, Huiyuan; Wen, Yu; Zhao, Yuhong; Chang, Qing (Frontiers in Nutrition, 2022)
Introduction The association between blood (serum or plasma) selenium concentrations and gestational diabetes mellitus (GDM) has been evaluated in some studies. However, the reported findings are debatable, and only case-control and cross-sectional studies were included. Objective This research aimed to assess the association between blood selenium levels and GDM by analyzing existing literature. To provide a reference for the prevention and treatment of GDM, we included prospective studies which are not included in previous studies to collate more high-quality evidence and better test the etiological hypothesis between blood Se concentrations and GDM. Methods The PubMed, EMBASE, and Web of Science databases were retrieved for literature up to September 2022, and relevant references were manually searched. Raw data from relevant studies were extracted, and a random effect model was adopted for meta-analysis. The total effects were reported as weighted mean differences. All data were analyzed using Stata 16.0 software. Results Fourteen studies involving 890 pregnant women with GDM and 1618 healthy pregnant women were incorporated in the meta-analysis. Pregnancies with GDM had significantly lower blood selenium levels than those with normal glucose tolerance (weighted mean difference = −8.11; 95% confidence interval: −12.68 to −3.54, P = 0.001). Subgroup analyses showed that the association between blood selenium levels and GDM was consistent in the residents of Asia and Africa, but not in European. This trend was significant in the second and third trimester subgroups, but not in the first trimester subgroup. Articles published in 2006–2015 also showed this trend, but those published before 2005 and 2016–2019 did not show significant results. This difference was evident in non-prospective studies, but not significant in prospective studies. Studies using the Carpenter and Coustan diagnostic criteria were consistent with this trend, whereas studies using other diagnostic criteria found no differences. In addition, in terms of blood selenium measurement methods, atomic absorption spectrometry showed more significant differences than other methods. In the subgroup analysis based on the sample size of included studies and the quality of the studies, each subgroup showed statistical differences. Conclusion Lower blood selenium concentrations are associated with GDM as shown in our study. Therefore, supplementing an appropriate amount of selenium may be helpful for GDM prevention and treatment.